(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2024)
This article explores the spatial dimensions of selfhood and the pathic felt-bodily resonance, emphasizing their role in understanding the connection between health and the environment. Adopting a phenomenological perspective, it provides an overview of the relationship between embodiment, spatiality, and affectivity and their alterations in mental conditions. It highlights the significance of alterations in affective permeability and embodiment, particularly in conditions such as schizophrenia, depression, and addiction, which lead to distortions in lived space and constrictions in the field of available affordances. It suggests the concept of ‘therapeutic atmospheres’ as those that open the corporal and emotional space of the patient and flexibilize the field of affective intensities navigated by them. It highlights the relevance of the therapists’ atmospheric competence and body availability to sustain the therapeutic space.